Pengaruh Penerapan Metode HOTS Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Matematika - Asdiana; Wahyu Novita Sari, Indah; abdussyukur, abdussyukur (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2023)
The purpose of this study was to determine the effect of the application of the HOTS method on mathematics learning outcomes. Data collection techniques using documentation tests using problem-based learning, as well as direct interviews with class teachers. This research is classified into experimental research, with a quantitative approach and one group experimental research design with pre-test and post-test results by trying to describe the influence of the HOTS method on learning outcomes in grade III students of State Elementary School 12 Bebesen. The subjects of this study numbered 20 people. Student learning outcomes using the HOTS method are more influential in improving student learning outcomes compared to not being given the HOTS learning method. Factors influencing learning outcomes at Bebesen State Primary School 12 are internal factors (interests and physical and health conditions) external factors (professional teachers, learning media, parents, and the environment). This study concludes that student learning outcomes show the mean or average pretest of student learning without applying the HOTS method, the score is 59.50, while the student's posttest score by applying the HOTS learning method, the score is 73.50.